Zinc oxide nanocrystal composite, dispersion liquid, thin film, electronic device, and composite forming method
By adding anhydrous zinc chloride and lithium hydroxide to the reaction solvent of zinc oxide nanocrystals and using a specific cleaning method, a zinc oxide nanocrystal complex containing only -OH, Cl, Li, and H ligands on the surface was successfully prepared, which solved the problem of complexity and low conductivity of the surface ligand of zinc oxide nanocrystals, and significantly improved its performance in electronic devices.
Patent Information
- Application Number
- CN202410972220.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-19
- Publication Date
- 2025-03-07
AI Technical Summary
The complexity of surface ligands of zinc oxide nanocrystals makes it difficult to control their nucleation growth rate, size and morphology, affecting their photoelectric properties, and the presence of organic ligands reduces conductivity and increases energy consumption.
Anhydrous zinc chloride and lithium hydroxide were reacted in a specific reaction solvent, and an initiator was added for stirring. The product was then washed by precipitation of poor solvent and dissolving of good solvent to obtain a zinc oxide nanocrystal complex containing only -OH, Cl, Li, and H ligands on the surface.
The surface of zinc oxide nanocrystals is achieved, the nanocrystal spacing is reduced, and the electron transmission conductivity is improved. Compared with the acetate ligand zinc oxide synthesized by traditional hydrothermal method, the film shows the effect of increasing the current density by more than one order of magnitude in electronic devices.
Smart Images

Figure CN119569103A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nano material preparation and application, and specifically relates to a zinc oxide nanocrystalline composite, a dispersion, a film, an electronic device and a method for forming the zinc oxide nanocrystalline composite. Background Art
[0002] Zinc oxide is a new type of II-VI group direct bandgap compound semiconductor. The bandgap of bulk zinc oxide at room temperature is about 3.37 eV, and its exciton binding energy is as high as 60 meV. In addition to traditional applications such as photocatalysis, sensors, solar cells, and light-emitting diodes, zinc oxide is also used in research fields such as cosmetics, biomarkers, and biodrug delivery due to its good biocompatibility. However, it is difficult to apply directly due to defects such as easy aggregation of nanoparticles, unstable surface chemical properties, lack of active functional groups on the surface, and poor repeatability. In order to solve these problems, it is urgent to study the surface structure of zinc oxide and its structure-activity relationship with the physical and chemical properties of zinc oxide.
[0003] The surface ligands of zinc oxide nanocrystals can not only regulate the nucleation growth rate, size, and morphology of nanocrystals, but also significantly affect the optoelectronic properties of nanocrystals. However, due to the diversity of nanocrystal surface components, the complexity of molecular structure and spatial distribution, and the constraints of characterization methods, the ligand chemical regulation of zinc oxide nanocrystals is still in a vague empiricist stage. Existing research methods generally provide information on the characteristic functional groups on the surface of zinc oxide nanocrystals through infrared spectroscopy. Until recently, researchers have begun to explore the application of solid-state nuclear magnetic resonance technology in the characterization of zinc oxide nanocrystal surface ligands.
[0004] However, even for zinc oxide nanocrystals synthesized by the common and simplest hydrothermal method, their surfaces contain many complex structures such as carboxylates, carboxylates, hydroxyls, and dangling bonds, which makes it very difficult to analyze the surface structure of zinc oxide nanocrystals. In addition, zinc oxide nanocrystals containing organic ligands will also cause the conductivity of the deposited film to decrease, resulting in increased energy consumption in the application of this material in optoelectronic devices. Therefore, the development of a new zinc oxide nanocrystal material with a simple surface and its preparation method will help deepen the understanding of zinc oxide surface chemistry at the molecular level, while improving the application value of zinc oxide materials in optoelectronic devices. Summary of the invention
[0005] The purpose of the present invention is to provide a zinc oxide nanocrystal composite, a dispersion, a film, an electronic device and a method for forming the zinc oxide nanocrystal composite in view of the defects of the prior art.
[0006] In order to achieve the above-mentioned purpose, the technical solution of the present invention is: as a first aspect, a zinc oxide nanocrystal composite is provided, comprising: a crystal core of a spherical wurtzite-type zinc oxide nanocrystal, and a ligand layer covering the surface of the crystal core, wherein the ligand layer only contains -OH ligands, Cl ligands, Li ligands and H ligands.
[0007] Furthermore, the diameter of the crystal core is 1 nm to 10 nm, and the particle size of the zinc oxide nanocrystalline composite is 2 nm to 12 nm.
[0008] Furthermore, the total mass of the ligands on the surface of the crystal core is 1% to 30% of the zinc oxide nanocrystal composite.
[0009] Furthermore, the H ligand is bound to the core body in the following manner: the H ligand is bound to a single Zn exposed on the crystal core body, or the H ligand is simultaneously bound to two Zn exposed on the crystal core body, or the H ligand is simultaneously bound to three Zn exposed on the crystal core body.
[0010] As a second aspect, a zinc oxide nanocrystal dispersion is provided, comprising the zinc oxide nanocrystal complex and a dispersion solvent, wherein the concentration of the zinc oxide nanocrystal complex is maintained at 10-60 mg / mL, and the dispersion solvent is a mixture of one or more of alcohols, dimethyl sulfoxide, and N,N-dimethylformamide in any proportion.
[0011] Furthermore, the alcohols include methanol, ethanol, propanol and isopropanol.
[0012] As a third aspect, a zinc oxide nanocrystalline film is provided, which is formed by spin coating and deposition of the nanocrystalline composite.
[0013] As a fourth aspect, an electronic device is provided, comprising a first electrode and a second electrode arranged opposite to each other, and a functional layer located between the first electrode and the second electrode, wherein the functional layer comprises the zinc oxide nanocrystalline thin film.
[0014] As a fifth aspect, a method for forming a zinc oxide nanocrystal composite is provided, comprising the following steps:
[0015] A. Add anhydrous zinc chloride and lithium hydroxide to a reaction solvent at 0°C to 80°C, then add an initiator, and stir to react for 1h to 24h; wherein the initiator is water or hydrogen peroxide, the molar ratio of the anhydrous zinc chloride to the lithium hydroxide is 1:1-2, and the molar ratio of the anhydrous zinc chloride to the initiator is 1:0.01-10;
[0016] B. washing the reaction product of step (A) by a method of precipitation with a poor solvent and dissolution with a good solvent to obtain the zinc oxide nanocrystal composite;
[0017] The reaction solvent and the good solvent are both composed of one or more of ethanol, methanol, dimethyl sulfoxide, and N,N-dimethylformamide mixed in any proportion, and the poor solvent is composed of ethyl acetate and an alkane solvent mixed in any proportion.
[0018] Furthermore, the step (B) is specifically as follows: adding a poor solvent to the reaction solution until the solution becomes turbid, centrifuging, discarding the supernatant, and adding the good solvent to the precipitate until it dissolves; repeating the above steps for a second washing, filtering, and obtaining the zinc oxide nanocrystal composite.
[0019] The beneficial effects of the present invention include: the surface of the zinc oxide nanocrystal composite of the present invention is pure and free of any organic ligands. The application of the novel organic ligand-free zinc oxide nanocrystal material of the present invention effectively reduces the spacing between nanocrystals deposited in a thin film state, improves the electron transmission conductivity, and compared with zinc oxide with acetate ligands synthesized by the traditional hydrothermal method, the film is used as a single carrier transport layer on electronic devices, which can achieve an increase of more than one order of magnitude in current density at the same voltage. The preparation method of zinc oxide nanocrystals of the present invention is simple and easy to operate, has low raw material cost, and is environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 is the UV-visible absorption spectrum of the zinc oxide nanocrystal dispersion prepared in Example 1 of the present invention;
[0021] Figure 2 is the infrared absorption spectrum of the zinc oxide nanocrystalline film prepared in Example 1 of the present invention;
[0022] Figure 3 is the carbon nuclear magnetic resonance spectrum of the zinc oxide nanocrystal composite prepared in Example 1 of the present invention;
[0023] Figure 4 is the hydrogen nuclear magnetic resonance spectrum of the zinc oxide nanocrystal composite prepared in Example 1 of the present invention;
[0024] Figure 5 is the UV-visible absorption spectrum of the zinc oxide nanocrystal dispersion prepared in Example 2 of the present invention;
[0025] Figure 6 is a schematic diagram of the structure of the electronic device prepared in Example 3 of the present invention;
[0026] Figure 7 is the UV-visible absorption spectrum of the zinc oxide nanocrystal dispersion prepared in Comparative Example 1 of the present invention;
[0027] Figure 8 is the current-voltage curve of the electronic device prepared in Example 3 of the present invention;
[0028] Fig. 9 is the current-voltage curve of the electronic device prepared in Comparative Example 1 of the present invention;
[0029] Fig.10 Schematic diagram of the structure of the zinc oxide nanocrystal composite prepared in an embodiment of the present invention. DETAILED DESCRIPTION
[0030] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those generally understood by those of ordinary skill in the art to which the present application belongs. The techniques, methods and devices known to those of ordinary skill in the relevant art may not be discussed in detail, but where appropriate, the techniques, methods and devices should be considered as part of the authorization specification. It should also be understood that the term "include / comprise" when used herein indicates the presence of the indicated features, wholes, steps, operations, units and / or components, but does not exclude the presence or addition of one or more other features, wholes, steps, operations, units and / or components and / or their combinations. It should also be understood that the following description of at least one exemplary embodiment is merely illustrative and is not intended to be any limitation on the present disclosure and its application or use. The present disclosure is not limited by any stated or implied theory given in the above-mentioned technical field, background technology, content of the invention or specific implementation.
[0031] The development of new materials depends on the guidance of mechanisms. The surface structure of zinc oxide nanocrystals directly affects the optoelectronic properties of zinc oxide materials. Therefore, a clear understanding of the surface structure of zinc oxide nanocrystals is crucial for regulating the properties of zinc oxide materials. However, the current research on the surface properties of zinc oxide nanocrystals is quite scarce. The reason is that the ligand composition is complex and it is difficult to distinguish the influence of each component. Therefore, the realization of zinc oxide nanocrystal materials with simple surface ligands and simple and controllable synthesis methods has important guiding significance for deepening our understanding of the zinc oxide surface. In addition, for thin film devices, the presence of organic ligands also hinders carrier transport. In order to improve the application value of zinc oxide materials in optoelectronic devices, it is necessary to develop zinc oxide materials with shorter chain lengths or even ligand-free ligands. The synthesis of zinc oxide nanocrystal materials without organic ligands plays a vital role in expanding the application range of zinc oxide materials.
[0032] The zinc oxide nanocrystal composite of the embodiment of the present invention comprises: a crystal core of a spherical wurtzite-type zinc oxide nanocrystal, and a ligand layer covering the surface of the crystal core, wherein the ligand layer only comprises -OH ligands, Cl ligands, Li ligands and H ligands. The diameter of the crystal core is 1nm to 10nm, and the particle size of the zinc oxide nanocrystal composite is 2nm to 12nm. The total mass of the ligands on the surface of the crystal core is 1% to 30% of the zinc oxide nanocrystal composite.
[0033] The H ligand is combined with the core body in the following manner: the H ligand is combined with a single Zn exposed on the core body nanocrystal, or the H ligand is combined with two Zn exposed on the crystal core body at the same time, or the H ligand is combined with three Zn exposed on the crystal core body at the same time.
[0034] In order to better preserve and transport, the present invention also proposes a zinc oxide nanocrystal dispersion. The zinc oxide nanocrystal dispersion comprises the zinc oxide nanocrystal compound disclosed in the present invention and a dispersion solvent, wherein the dispersion solvent is one or more of alcohols such as methanol, ethanol, propanol, isopropanol, dimethyl sulfoxide, and N,N-dimethylformamide mixed in any proportion. These dispersion solvents also do not contain long carbon chain organic ligands.
[0035] The zinc oxide nanocrystalline composite of the present invention can be further processed into a thin film. For example, the zinc oxide nanocrystalline composite disclosed in the present invention can be formed into a zinc oxide nanocrystalline thin film by spin deposition.
[0036] The electronic device containing the zinc oxide nanocrystalline thin film of the present invention comprises: a first electrode and a second electrode arranged opposite to each other, and a functional layer located between the first electrode and the second electrode. The functional layer comprises the zinc oxide nanocrystalline thin film of the present invention. The thin film is usually used as a single carrier transport layer, and only electrons exist in the carrier transport under normal working conditions, and no holes exist.
[0037] The method for forming the zinc oxide nanocrystal composite of the present invention mainly comprises the following steps A and B.
[0038] Step A. Add anhydrous zinc chloride and lithium hydroxide to a reaction solvent at 0°C to 80°C, and then add an initiator, wherein the initiator is water or hydrogen peroxide, and stir to react for 1h to 24h. The molar ratio of anhydrous zinc chloride to the lithium hydroxide is 1:1 to 1:2. The molar ratio of anhydrous zinc chloride to the initiator is 1:0.01 to 1:10.
[0039] Water can act like an initiator. The reaction will not occur without additional water. The mechanism is speculated to be the following process. First, water coordinates to Zn, reducing the leaving energy of Cl and activating the hydrolysis site of Zn. Then the hydroxide of the added base can attack Zn to form hydroxyl groups, which can produce further hydrolysis nucleation reaction. Additional water can also be formed during the hydrolysis process to help the cycle of the process. The more water is initially added, the faster the reaction rate. The specific process can be referred to as follows:
[0040] ZnCl2+H2O→(Cl—Zn·OH2) + +Cl -
[0041] (Cl—Zn·OH2) + +LiOH→Cl—Zn—OH+Li + +H2O
[0042] n Cl—Zn—OH+(n-1)LiOH→Cl—(ZnO) n —H+(n-1)LiCl+(n-1)H2O
[0043] Step B. Use a poor solvent precipitation and good solvent dissolution method to wash the reaction product of step A to obtain the zinc oxide nanocrystalline composite. The washing process is to remove the excess LiCl generated by the reaction and the unreacted precursors, such as Cl-Zn-OH, etc., in order to purify the zinc oxide nanocrystalline composite.
[0044] First, a poor solvent is added to the reaction solution until the solution becomes turbid, centrifuged, the supernatant is discarded, and the precipitate is dissolved with a good solvent; then a second washing is performed, a poor solvent is added to the resulting solution again until the solution becomes turbid, centrifuged, the supernatant is discarded, the precipitate is dissolved with a good solvent, and filtered to obtain the zinc oxide nanocrystalline composite. The reaction solvent and the good solvent are one or more of ethanol, methanol, dimethyl sulfoxide, and N,N-dimethylformamide mixed in any proportion, and the poor solvent is ethyl acetate and an alkane solvent mixed in any proportion.
[0045] Hereinafter, the embodiments are described in more detail with reference to specific examples. However, they are illustrative examples of the present disclosure, and the present disclosure is not limited thereto.
[0046] Example 1: Synthesis of novel organic ligand-free zinc oxide nanocrystals
[0047] Synthesis: Weigh 1.5mmol of anhydrous zinc chloride and dissolve it in 15mL of dimethyl sulfoxide (DMSO); continue to weigh 2.5mmol of lithium hydroxide (LiOH) and dissolve it in 25mL of ethanol solution; after all the LiOH is dissolved, add it all to the DMSO solution containing anhydrous zinc chloride, heat the solution to 50°C, add 200μL of water, and react at 50°C for 2h. In this embodiment, the molar ratio of anhydrous zinc chloride to lithium hydroxide is 3:5, and the molar ratio of anhydrous zinc chloride to initiator is 1:7.4.
[0048] Purification: Take 5 mL of the reaction stock solution, add 5 mL of ethyl acetate and 15 mL of heptane, centrifuge, and discard the supernatant; dissolve the precipitate in 1 mL of ethanol, add 1 mL of ethyl acetate and 3 mL of heptane, centrifuge, and discard the supernatant; finally, dissolve the precipitate in 300 μL of ethanol solution.
[0049] from Figure 1 It can be seen that the zinc oxide nanocrystals synthesized by this method have a strong quantum confinement effect, and the exciton absorption peak is around 303nm. The zinc oxide nanocrystal solution was made into a thin film by spin coating and then the infrared absorption spectrum was tested, such as Figure 2 Shown, only 1642cm -1 The in-plane bending vibration of water and 3480cm -1 The left and right symmetrical and asymmetrical stretching vibrations or the hydroxyl vibrations on the surface of zinc oxide. The zinc oxide nanocrystal solution was dried in a vacuum oven to prepare solid powder for solid nuclear magnetic resonance testing. Figure 3 It can be seen that there is no signal in the carbon spectrum, indicating that it does not contain any carbon-containing ligands. Figure 4 It can be seen that the hydrogen spectrum contains information about four peaks, indicating that the zinc oxide has fewer hydrogen-containing surface states and is suitable as a blank reference for studying the surface information of zinc oxide.
[0050] Example 2: Synthesis of novel organic ligand-free zinc oxide nanocrystals of different sizes
[0051] The difference from Example 1 is that the synthesis steps are: 2 mmol of anhydrous zinc chloride is dissolved in 20 mL of DMSO; 2 mmol of LiOH is dissolved in 20 mL of ethanol. In this example, the molar ratio of anhydrous zinc chloride to lithium hydroxide is 1:1, and the molar ratio of anhydrous zinc chloride to initiator is 1:5.6.
[0052] like Figure 5 As shown in the figure, the exciton absorption peak of the zinc oxide nanocrystals synthesized by this method is around 325nm, that is, the size of the nanocrystals becomes larger. The reason is that the zinc salt content in the synthetic raw materials increases, indicating that the size of the new organic ligand-free zinc oxide nanocrystals can be adjusted by changing the ratio of ZnCl2 to LiOH in the reaction raw materials.
[0053] Example 3: Preparation of single carrier device
[0054] In order to verify the application potential of this new type of organic ligand-free zinc oxide nanocrystals in thin film devices, the material can be deposited on Figure 6 In the device structure shown, the specific steps are as follows.
[0055] 1. Substrate cleaning: Wipe the indium tin oxide (ITO) substrate with a dust-free cloth dipped in ethanol, then ultrasonically clean it in acetone, deionized water, and ethanol for 10 minutes, then blow dry it with a nitrogen gun, and finally use oxygen plasma to clean it for 10 minutes.
[0056] 2. Ethoxylated polyethyleneimine (PEIE): A 1 mg / mL PEIE isopropanol solution was spin coated on ITO at 2,000 rpm for 40 s, then annealed at 50° C. in air for 15 min, and then rinsed with 20 μL ethanol by spin coating at 2,000 rpm.
[0057] 3. Zinc oxide electron transport layer: The novel zinc oxide nanocrystal solution was spin coated on the PEIE at a rotation speed of 2,000 rpm for 40 s, and the absorbance of the solution at 280 nm was 250-300, without annealing treatment.
[0058] 4. Aluminum electrode: Transfer the prepared film to the evaporation chamber and evacuate to ~6×10 -7 Torr, and then evaporated 100nm Al electrode, the evaporation rate was controlled at
[0059] 5. After the evaporation is completed, the device is encapsulated with 3335 UV curing adhesive that does not contain organic acid to eliminate the positive aging phenomenon of the zinc oxide layer caused by acid reported in the literature.
[0060] Comparative Example 1
[0061] The difference between Comparative Example 1 and Example 1 is that the most common hydrothermal method is used to synthesize ZnO nanocrystals. Specifically, first weigh 1mmol Zn(Ac)2·2H2O in a 100mL three-necked flask, add 20mL of dimethyl sulfoxide (DMSO) solvent, and stir for about 10min in a constant temperature water bath at 50°C until it is completely dissolved. Then, 3mmol LiOH solid is placed in 20mL of ultra-dry ethanol solvent. After the LiOH solid is completely dissolved, the ethanol solution containing LiOH is directly poured into the reaction three-necked flask, and the reaction is continuously stirred at a constant temperature of 50°C for 1 hour. After the reaction is completed, 2mmol glacial acetic acid is added to the reaction flask to neutralize the excess alkali in the reaction system. Then purify twice with ethyl acetate / ethanol. The UV-visible absorption spectrum of the final nanocrystal solution is as follows Figure 7As shown, its exciton absorption peak is also at 303 nm, proving that the size of the nanocrystal is close to that synthesized in Example 1.
[0062] Testing single carrier devices:
[0063] The current density-voltage curve of the single-carrier device was measured using Keithley 2400, and the current-voltage curve of the single-carrier device between 0-4V was scanned with a step size of 0.05V. Fig. 9 As shown in the figure, it can be seen that the current density of the single-electron device prepared by the zinc oxide material with traditional acetate ligand is only 9.46 mA cm at 3 V. -2 . And if Figure 8 As shown in Figure 2, the single-electron device prepared with the new organic ligand-free zinc oxide material can achieve a current density of 265 mA cm at a voltage of 3 V. -2 , one and a half orders of magnitude higher, proving that eliminating carbon-containing ligands can greatly improve the conductivity of zinc oxide materials. Calculations show that at 10 mA cm -2 The working power density of the single-electron device prepared by the traditional acetate ligand zinc oxide material is about 30mW cm -2 , while the single electron device made of new organic ligand-free zinc oxide material has an operating power density of only 12.5 mW cm -2 , proving that the new zinc oxide material can greatly reduce power consumption loss as a carrier transport layer.
Claims
1. A zinc oxide nanocrystal composite, characterized in that: include: A crystal core of a spherical wurtzite-type zinc oxide nanocrystal, and a ligand layer covering the surface of the crystal core, wherein the ligand layer only contains -OH ligands, Cl ligands, Li ligands and H ligands.
2. The zinc oxide nanocrystal composite according to claim 1, characterized in that: The diameter of the crystal core is 1 nm to 10 nm, and the particle size of the zinc oxide nanocrystalline composite is 2 nm to 12 nm.
3. The zinc oxide nanocrystal composite according to claim 1, characterized in that: The total mass of the ligands on the surface of the crystal core is 1% to 30% of the zinc oxide nanocrystal composite.
4. The zinc oxide nanocrystal composite according to claim 1, characterized in that: The H ligand is combined with the core body in the following manner: the H ligand is combined with a single Zn exposed on the crystal core body, or the H ligand is combined with two Zn exposed on the crystal core body at the same time, or the H ligand is combined with three Zn exposed on the crystal core body at the same time.
5. A zinc oxide nanocrystal dispersion, characterized in that: The method comprises the zinc oxide nanocrystal composite according to any one of claims 1 to 4 and a dispersing solvent, wherein the concentration of the zinc oxide nanocrystal composite is maintained at 10-60 mg / mL, and the dispersing solvent is one or more of alcohols, dimethyl sulfoxide, and N,N-dimethylformamide mixed in any proportion.
6. The zinc oxide nanocrystalline dispersion according to claim 5, characterized in that: The alcohols include methanol, ethanol, propanol and isopropanol.
7. A zinc oxide nanocrystalline film, characterized in that: The nanocrystalline composite is formed by spin coating deposition according to any one of claims 1 to 4.
8. An electronic device, characterized in that: The electronic device comprises a first electrode and a second electrode which are arranged opposite to each other, and a functional layer located between the first electrode and the second electrode, wherein the functional layer comprises the zinc oxide nanocrystalline thin film according to claim 7.
9. A method for forming a zinc oxide nanocrystalline composite, characterized in that: The steps include: A. Add anhydrous zinc chloride and lithium hydroxide to a reaction solvent at 0°C to 80°C, then add an initiator, and stir to react for 1h to 24h; wherein the initiator is water or hydrogen peroxide, the molar ratio of the anhydrous zinc chloride to the lithium hydroxide is 1:1-2, and the molar ratio of the anhydrous zinc chloride to the initiator is 1:0.01-10; B. washing the reaction product of step (A) by a method of precipitation with a poor solvent and dissolution with a good solvent to obtain the zinc oxide nanocrystal composite; The reaction solvent and the good solvent are both composed of one or more of ethanol, methanol, dimethyl sulfoxide, and N,N-dimethylformamide mixed in any proportion, and the poor solvent is composed of ethyl acetate and an alkane solvent mixed in any proportion.
10. The forming method according to claim 9, characterized in that: The step (B) specifically comprises: adding a poor solvent to the reaction solution until the solution becomes turbid, centrifuging, discarding the supernatant, and adding the good solvent to the precipitate until it dissolves; repeating the above steps for a second washing, filtering, and obtaining the zinc oxide nanocrystal composite.
Citation Information
Patent Citations
Method for preparing zinc oxide nano thin film under low-temperature condition and application of zinc oxide nano thin film
CN107176621A
Zinc oxide nanocrystal, zinc oxide nanocrystal composition, preparation method thereof, and electroluminescent device
CN110484233A
Zinc oxide nano material, preparation method thereof and luminescent device
CN113838985A
Preparation method of quantum dot light-emitting diode
CN114695719A
Preparation method of quantum dot light-emitting diode
CN114695821A